Role of Gibberellic Acid (GA₃) in enhancing growth and yield of hydroponically grown lettuce (Lactuca sativa L.) - Fadillah, Resti; Wildani, Rizka; Salsabila, Varaditta Putri Zahra (Jurnal Ilmu Pertanian, 2024)
Gibberellin (GA₃) is a growth hormone that is essential in plant physiological processes. At present, gibberellins are employed in commerce to enhance the physical traits and yield of various vegetable, horticultural, ornamental, and medicinal crops. This research aimed to study the effects of gibberellin application on the morphological characteristics and yield of lettuce plants. The study was arranged in a Completely Randomized Design (CRD) with six treatments of gibberellins concentration with a hydroponic system, namely: G0 = control, G1 = 20 ppm, G2 = 40 ppm, G3 = 60 ppm, G4 = 80 ppm, and G5 = 100 ppm, and each treatment consisted of four replications. This research was conducted in May–July 2023 at the Kemuning Greenhouse, Belu Regency, East Nusa Tenggara. GA₃s were sprayed twice at 2 weeks after sowing and 1 week after transplanting. The results showed that the highest GA₃ concentration (100 ppm) had a negative impact on plant morphology and yield, producing the smallest number of leaves, too long stem, pale green leaves, and the lowest fresh weight. Meanwhile, GA₃ concentration of 40 ppm resulted in the highest number of leaves. However, this increase is not directly proportional to the fresh weight of the leaves. GA₃ concentration of 40 ppm resulted in the best and most efficient yield of leaves and fresh weight, making it highly recommended.